The African Americans and the Quest for Identity - Benazouz, Somia (My University, 2018)
The quest of identity has been always a controversial issue in shaping the history of African Americans. Through which blacks desired to challenge the dominant race “white race”. From the post emancipation of slavery, the status of Blacks had transformed from object –article of merchandize- to be a qualified subject holding cultural backgrounds. Although the Blacks were excluded from the American society racism, segregation, and white prejudices, thus they strived to find pragmatic and solutions and strategies to be included within the social, cultural, and political community. The 20th century was an era of maturation about racial, political, and cultural uplifting. The quest for cultural and political identities were embodied through black movements such as the Harlem Renaissance and the Civil Right Movement, as being the direct roads to search for cultural and political inclusion. Furthermore, black leaders and artists had an influential role in transforming the stereotypes of black race’s inferiority to black’s racial pride.
Keywords: Black race movement; Black power; Historical and culturel contexts